International Conference on "Holography Meets Advanced Manufacturing" - Anand, Vijayakumar; Jayavel, Amudhavel; Palm, Viktor; Gopinath, Shivasubramanian; Bleahu, Andrei; Rajeswary, Aravind; Kukli, Kaupo; Balasubramani, Vinoth; Smith, Daniel; Ng, Soon; Juodkazis, Saulius (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This Proceedings reprint is focused on the latest developments in the topics of imaging technology, advanced manufacturing, and medical diagnosis. The evolving interdisciplinary research between the three topics is discussed.